3D printing and inspection - Costa, Manuel F. M. (2016)
Non-destructive dimensional inspection of surfaces is an issue of utmost importance in a large number of situations in R&D and at the industrial world. An increasing number of surfaces and sur-face types must be microtopographically characterized in a non-destructive non-invasive way [1]. Statistical parameters, both 2D and 3D, are fundamental to a useful quantitative characterization of the surface’ relief. However the two and tridimensional magnified representation of the microtopo-graphic structure of the surface, allowing a comfortable and detailed visualization of the relief structure, gives very meaningful insights and is more and more requested.